2018
DOI: 10.2147/itt.s134834
|View full text |Cite
|
Sign up to set email alerts
|

Antibody targeting of phosphatidylserine for the detection and immunotherapy of cancer

Abstract: Phosphatidylserine (PS) is a negatively charged phospholipid in all eukaryotic cells that is actively sequestered to the inner leaflet of the cell membrane. Exposure of PS on apoptotic cells is a normal physiological process that triggers their rapid removal by phagocytic engulfment under noninflammatory conditions via receptors primarily expressed on immune cells. PS is aberrantly exposed in the tumor microenvironment and contributes to the overall immunosuppressive signals that antagonize the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 115 publications
0
41
0
Order By: Relevance
“…On the basis of our previous reports that TAMs, acting as PS sensing receptors, could induce epithelial efferocytosis and the subsequent upregulation of PD-L1, we propose that in vivo, combinations of PS targeting, TAM therapeutics, and anti-PD-L1/PD-1 may have additive or synergistic activities as combined therapeutics. Indeed, prior studies by Gray and colleagues have shown that combined PS targeting antibodies (upstream of TAM receptors) with anti-PD-1 function synergistically in a syngeneic breast cancer model (39,40). The current study shows that Tyro3, Axl, and Mertk are differentially expressed on several cell subtypes that contribute to the tumor microenvironment, whereby Axl is preferentially expressed on E0771 tumor cells, while macrophages, including peritoneal macrophages, bone marrow-derived macrophages, and tumorassociated macrophages have higher Mertk/Axl ratios.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of our previous reports that TAMs, acting as PS sensing receptors, could induce epithelial efferocytosis and the subsequent upregulation of PD-L1, we propose that in vivo, combinations of PS targeting, TAM therapeutics, and anti-PD-L1/PD-1 may have additive or synergistic activities as combined therapeutics. Indeed, prior studies by Gray and colleagues have shown that combined PS targeting antibodies (upstream of TAM receptors) with anti-PD-1 function synergistically in a syngeneic breast cancer model (39,40). The current study shows that Tyro3, Axl, and Mertk are differentially expressed on several cell subtypes that contribute to the tumor microenvironment, whereby Axl is preferentially expressed on E0771 tumor cells, while macrophages, including peritoneal macrophages, bone marrow-derived macrophages, and tumorassociated macrophages have higher Mertk/Axl ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies by Herrmann and colleagues showed that interfering with PS-mediated efferocytosis by masking PS with annexin V favors an anti-tumor host response, possibly by delaying clearance and possibly promoting a sterile inflammation by the release of DAMPs by secondary necrotic death (i.e., ICD mimicry) [ 127 , 128 , 129 ]. More recently, a series of PS-targeting mAbs and PS-targeting biomolecules have been developed that can interfere with PS-mediated immunosuppression and facilitate the induction of an innate and adaptive anti-tumor immune response (reviewed in references [ 52 , 130 , 131 ]). While it might be expected that PS-targeting mAbs simply bind to and mask PS on the surface of apoptotic (and other PS-positive) cells to disrupt immunosuppressive signals from PS receptors such as TAMs and TIMs, emerging research identifies a more complex biological function for PS-targeting mAbs.…”
Section: Modulation Of Ps Signaling and Efferocytosis As An Anti-tmentioning
confidence: 99%
“…Belzile et al introduce a novel therapeutic approach for cancer by antibody targeting of phosphatidylserine (PS). 1 …”
mentioning
confidence: 99%
“…In another study that deals with the mechanism for fetal loss in APS, exposure of rat embryos and their yolk sacs to aPS led to an inhibition of the yolk sac growth and a higher apoptosis rate compared with the control group. 5 With this knowledge, cancer immunotherapy by antibody targeting the PS 1 raises questions regarding the development of thromboembolic events in patients who accept this therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation